Traditional Administrative Leadership Ninik Mamak Suku Nan Tujuh in Public Service The Kepenghuluan Rantau Bais Rokan Hilir Riau Indonesia - Latip, Latip; Ramli, Zuliskandar; Musa, Mhd. Faizal; Saputra, Trio (Jurnal Mamangan, 2025)
Traditional leadership, as a vital component of a society’s cultural and social heritage, has become an area of increasing focus amidst the rapid changes of modern times. This study examines the leadership of Ninik Mamak from the Suku Nan Tujuh in  Public Service The Kepenghuluan Rantau Bais, which holds a rich cultural legacy rooted in its traditional leadership system. The primary aim of this research is to explore and understand the traditional administrative leadership model of the Ninik Mamak Suku Nan Tujuh in the context of Kepenghuluan Rantau Bais. Utilizing a comprehensive qualitative approach, data were collected through in-depth interviews with local leaders, community members, and traditional figures. Historical and documentary data were also analyzed to trace the evolution and transformation of the traditional leadership system.The findings reveal that the traditional administrative leadership model in Kepenghuluan Rantau Bais remains active and plays a critical role in preserving social harmony and fulfilling essential functions within the community. However, the research also highlights challenges posed by modernization, urbanization, and shifting social values, which could potentially threaten the sustainability of this leadership model. This study provides valuable insights into traditional leadership practices in Kepenghuluan Rantau Bais and sheds light on the broader roles and challenges faced by indigenous communities in preserving their cultural heritage. The research emphasizes the importance of safeguarding and fostering cultural and social traditions in response to the dynamic changes of the modern era.